Phenotypic and genotypic characterization of Escherichia Coli O111 serotypes - Alikhani, Mohammad Yousef (Research Institute for Gastroenterology and Liver Diseases, 2011)
AIM: The purpose of this study was to characterize phenotypically and genotypically the serotypes of the E. coli O111 associated with diarrheal disease and assess the variation among serotypes in terms of specific virulence factors and HeLa cells adherence patterns. BACKGROUND: Escherichia coli O111 serogroups are prevalent in endemic or sporadic cases of diarrhea, especially in developing areas. PATIENTS AND METHODS: A total of 54 strains of E. coli O111 isolated from diarrheal and healthy cases were included in this study. Flagella antigens of motile and non-motile strains were identified by fliC-RFLP method (H types) and confirmed with agglutination test using H-specific antisera. All strains were tested for the presence of 5 different gene regions associated with virulence (eaeA, eaeB, bfpA, sxt and EAF plasmid) by PCR and the patterns of bacterial attachment to HeLa cells was assayed in cell culture. RESULTS: Of 54 E. coli O111 strains, 89% were typeable with standard H antisera and the remaining 11% of strains were non-motile (H -). Twenty-three different H type were distinguished among the O111 strains by PCR-RFLP. The most common serotypes included H21, H9, H2, H6 and H12 (48%). Serotypes O111:H9 were represented by strains with 2 patterns of virulence genes (eaeA(+) /bfpA(+)/EAE(+), and eaeA(+) /bfpA(-)/EAE(-)) and serotype H14 was represented by strains with the single eaeA(+) /bfpA(+)/EAE(-) combination. Four distinct patterns of adherence were distinguished: LA, LLA, AA and DA. All of serotypes with the eaeA(+) /bfpA(+)/EAE(+), or eaeA(+)/bfpA(+)/EAE(-), combination isolated from children with diarrhea exhibited the LA pattern, and serotypes with eaeA(+)/bfpA(-)/EAF(-) showed the LLA, while the majority of the strains isolated from healthy cases exhibited the DA, AA and NA patterns. CONCLUSION: Strains of this O serogroup represented a diverse of serotypes with a variety of virulence factors and mechanisms of pathogenesis.